Bio-Oil Production from Cirsium yildizianum through Pyrolysis in a Fixed-Bed Reactor - Aysu, Tevfik; Bengü, Aydin Sükrü (Journal of Applied Solution Chemistry and Modeling, 2014)
Pyrolysis of Cirsium yildizianum samples were carried out in a fixed-bed tubular reactor with (tincal, colemanite and ulexite) and without catalyst catalyst at three different temperatures (350, 450, 550 oC) with a constant heating rate of 50 oC/min. The yields of bio-char, bio-oil and gas produced along with the compositions of the resulting bio-oils were determined by elemental, Fourier transform infrared spectroscopy (FT-IR) and Gas chromatography/ mass spectrometry (GC–MS). The effects of pyrolysis parameters including temperature and catalyst on product yields were investigated. The results indicate that both temperature and catalyst had signficant effect on conversion of Cirsium yildizianum into solid, liquid and gas products. The highest liquid (bio-oil) yield of 40.62% including aqueous phase was obtained in the presence of colemanite (10%) as catalyst at 550 oC. 79 different compounds were identified by GC-MS in bio-oils obtained at 550 oC.